MENINGKATKAN KETERAMPILAN LITERASI MENULIS TEKS PROSEDUR MENGGUNAKAN KOMBINASI MODEL PEMBELAJARAN PBL DAN PAP - Irma Febriana; Radiansyah (STKIP Subang, 2024)
This research uses Classroom Action Research which aims to improve teacher activity, student activity, writing skills and student learning outcomes using the Problem Based Learning (PBL) and Picture and Picture (PaP) learning model which is implemented in class IV at SDN Sungai Miai 4 Banjarmasin with a total of 22 students. Data collection techniques were carried out using observation and tests. The results of this research show that teacher activity at meeting 3 obtained a percentage of 96% with the criteria